Hubungan Nilai Konsolidasi dan Nilai Kuat Tekan Bebas pada Tanah Lempung yang Disubtitusi Material Pasir - Kurniawan, Dedy; Iswan, Iswan; Setyanto, Setyanto (Universitas Lampung, 2015)
This study was conducted to determine the behavior of reduction and compressive strength in claywhich is substituted with sand material and to see the correlation between the value ofconsolidation and the compressive strength on the soil. Because the clay when getting loadingthere will be a significant reduction in soil that affects the reduction in carrying capacity orcompressive strength of the soil. In this study used clay from the village of Belimbing Sari, Jabungdistrict, East Lampung with the coordinates of 105° 39 '10.74